Spatiotemporal composition and diversity of endophyte communities in Dracaena cambodiana on Hainan Island - Sipeng Li; Yang Liu; Xin Yang; Yun Yang; Junxiang Peng; Yanhong Xu; Jianhe Wei; Jianhe Wei (Frontiers in Microbiology)
IntroductionDracaena cambodiana produces a red resin known as Dragon’s blood, which is used worldwide in traditional medicine and as a dye. The role of endophytes in the resin-formation process remains underexplored. Understanding the endophyte communities and their functional roles in resin production could enable the development of efficient induction techniques for resin production.MethodsIn this study, ITS and metagenomic sequencing analyzed endophyte communities’ characteristics and functional traits in different tissues and D. cambodiana across multiple wild populations on Hainan Island.ResultsWe identified distinct fungal genera that were dominant in different tissues. Following injury, we observed significant changes in the expression of endophytic fungal genes. These changes indicated that metabolic pathways associated with resin metabolism, sucrose metabolism, signal transduction, and phenylalanine metabolism were likely involved in resin formation. Additionally, several glycosylation gene families were upregulated in the post-injury endophytic communities, which suggests a role in flavonoid transport and the reduction of autotoxic effects.DiscussionOur results suggest that endophytes play a vital role in the resin-formation process of D. cambodiana. Isolating specific endophytes or using synthetic communities could potentially improve resin yields and avoid pathogenic fungi, ensuring safety. The findings from this study provide a theoretical basis for the development of high-efficiency resin induction techniques by targeting the dynamic changes in endophyte communities across tissues, regions, and resin formation stages.